Analysis of Drug Metabolizing Gene Panel in Osteosarcoma Patients Identifies Association Between Variants in SULT1E1, CYP2B6 and CYP4F8 and Methotrexate Levels and Toxicities - Hurkmans, Evelien G. E.; Klumpers, Marije J.; Vermeulen, Sita H.; Hagleitner, Melanie M.; Flucke, Uta; Schreuder, H. W. Bart; Gelderblom, Hans; Bras, Johannes; Guchelaar, Henk-Jan; Coenen, Marieke J. H.; te Loo, D. Maroeska W. M. (Frontiers in Pharmacology, 2020)
High-dose methotrexate is a cornerstone agent in the chemotherapeutic treatment of patients with osteosarcoma. However, patients often develop methotrexate-induced toxicities. We aim to identify determinants of methotrexate-induced toxicities in osteosarcoma patients by investigating the relation between drug plasma levels, methotrexate-induced toxicities, and germline variants in genes related to drug absorption, distribution, metabolism and elimination. A cohort of 114 osteosarcoma patients was genotyped for 1,931 variants in 231 genes using the Drug Metabolism Enzymes and Transporters Plus array. Methotrexate plasma levels and laboratory measurements during and after high-dose methotrexate treatment concerning renal function, liver damage and myelopoiesis to reflect toxicity outcomes were obtained. 113 patients and a subset of 545 variants in 176 genes passed quality control checks. Methotrexate plasma levels showed associations with creatinine, alanine aminotransferase, and hemoglobin. Genetic variant rs3736599 in the 5’-untranslated region of SULT1E1 was associated with lower 48 hour methotrexate plasma levels (coef -0.313 [95% CI -0.459 – -0.167]; p=2.60×10-5). Association with methotrexate-induced decreased thrombocyte counts was found for two intronic variants in CYP2B6 (rs4803418 (coef -0.187 [95% CI -0.275 – -0.099]; p=3.04×10-5) and rs4803419 (coef -0.186 [95% CI -0.278 – -0.093]; p=8.80×10-5)). An association with increased thrombocyte counts was identified for the intronic variant rs4808326 in CYP4F8 (coef 0.193 [95% CI 0.099 – 0.287]; p=6.02×10-5). Moreover, a secondary analysis with a binary approach using CTCAE toxicity criteria, resulted in a nominal significant associations (p<0.05) for two out of three variants (rs4803418 and rs4808326). This is the first study to identify genetic variants in SULT1E1, CYP2B6 and CYP4F8 to be associated with methotrexate pharmacokinetics and toxicities. Validation of these variants in an independent cohort and further functional investigation of variants in the identified genes is needed to determine if and how they affect methotrexate plasma levels and the development of methotrexate-induced toxicities.